Nitrogen-rich porous polymer adsorbent containing rigid fluorene structure as well as preparation method and application of nitrogen-rich porous polymer adsorbent
By introducing a rigid fluorene structure into the adsorbent material, the adsorption speed and quantity are improved, the stability and renewability are enhanced, and the existing adsorbent materials are solved, with slow speed, limited amount and poor stability when adsorbing acidic orange 7, and efficient, economical and environmentally friendly adsorption effects are achieved.
Patent Information
- Application Number
- CN202510028080.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-08
AI Technical Summary
The existing adsorbent materials are slow in adsorbing acidic orange 7 and have limited amounts. They are poor in stability in complex wastewater environments, difficult to regenerate, complex preparation process, and expensive raw materials.
A class of nitrogen-rich porous polymer adsorbent materials containing rigid fluorene structures were designed. By introducing rigid fluorene structural units on the polymer main chain, the specific surface area and thermal stability of the adsorbent were improved, and the green preparation method was used to make the material renewable.
The adsorption speed and quantity are significantly improved, the adsorption performance under different environmental conditions is enhanced, the preparation process is simplified, the cost is reduced, and the renewability and recyclability of the material is improved.
Smart Images

Figure BDA0005233352380000031 
Figure BDA0005233352380000081 
Figure FDA0005233352370000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer adsorbent materials, and in particular relates to a nitrogen-rich porous polymer adsorbent containing a rigid fluorene structure, a preparation method thereof, and an application in the adsorption field. Background Art
[0002] Synthetic dyes are important basic compounds that can attach themselves to the surface of an object or fabric to give color, and are widely used in various textile, papermaking, leather, food processing, plastics, cosmetics, rubber, printing and dyeing manufacturing industries. The consumption rate of azo dyes in the textile industry is 60%-70%, making it the most consumed dye. Acid Orange 7 (AO7, C 16 H 11 N2NaO4S), also known as Orange II, is a widely used azo dye and is often used to dye fabrics such as wool, silk and nylon, giving the fabrics a bright orange color. Although this type of industrial dye has important application value, it is prohibited to be used in food processing. If it is ingested into the human body through improper means, it will cause damage to organs such as the gastrointestinal tract of the human body; if it enters the environment such as water bodies, it will be toxic to aquatic organisms and may affect the ecological balance. Due to its harmful effects on humans and animals, people have aroused interest in the treatment of wastewater containing this dye. In the past three decades, some physical, chemical and biological decolorization methods have been reported, but few methods have been accepted by the papermaking and textile industries. Among the many dye removal technologies, adsorption is the preferred method because different types of coloring materials can be removed with good results. Adsorption is an equilibrium separation process. It is not only an effective method for water decontamination applications, but also the adsorption process does not produce new harmful substances. In addition, adsorption has obvious advantages in terms of initial cost, design flexibility and simplicity, operability and insensitivity to toxic pollutants.
[0003] Nitrogen-rich organic polymers formed by the Schiff base reaction of amines and aldehydes are an important class of organic porous adsorption materials (OPMs). This type of porous covalent organic polymer material can form a periodic network structure by modularizing different organic ligand units and exhibits high adsorption performance. It has been favored by researchers in recent years. OPM is different from regular chain macromolecules because permanent porosity can be obtained without post-treatment or multi-step cross-linking. The advantages of low density, high porosity, high specific surface area and stability make OPM materials show good application potential in the fields of gas separation and storage, catalysis, optoelectronics and medicine. Among these material systems, triazine-based porous organic materials have rich nitrogen content and highly stable chemical structure. They are a class of porous organic polymer materials with broad application prospects. They are also one of the porous materials with high application prospects in the adsorption of dye pollution in water bodies.
[0004] In terms of adsorption applications, for the adsorption of Acid Orange 7, the adsorption material needs to have a series of specific properties. First, it must have a high specific surface area and a porous structure. For example, the iron-zinc composite metal organic carbon material provides many contact sites for the acid orange 7 molecules by virtue of its porous characteristics and large specific surface area, making it easy for it to enter the interior. Secondly, it is best to have specific functional groups such as amino groups and hydroxyl groups on the surface that can form hydrogen bonds, π-π stacking and other interactions with acid orange 7. Furthermore, the material must have good chemical stability, stable chemical properties under different environmental conditions such as pH values and temperatures, and not decompose or deteriorate, to ensure reliable and lasting adsorption; it must also have strong mechanical stability, not easy to break or wear after mechanical actions such as stirring and filtering, and maintain structural integrity and adsorption performance. In addition, in order to reduce costs and reduce secondary pollution, the adsorption material should be renewable and recyclable, and the adsorbed acid orange 7 can be desorbed and restored to adsorption capacity by simple methods such as acid-base elution and heating.
[0005] Compared with some existing similar adsorption materials, the present invention has essential differences in application. On the one hand, there is a significant improvement in adsorption performance. The new adsorption material may have a higher adsorption capacity, a faster adsorption rate or a wider applicable pH range. For example, compared with traditional activated carbon, it can more efficiently remove acid orange 7. At the same time, it is more economical and environmentally friendly. The preparation and use process adopts green methods and is cheap. The post-adsorption saturation treatment method has little impact on the environment and is in line with sustainable development.
[0006] In general, the technical problems that the present invention actually aims to solve are clear. First, in view of the slow adsorption speed and limited adsorption capacity of existing adsorbent materials, we are committed to developing a material that can quickly and massively adsorb Acid Orange 7, improve wastewater treatment efficiency and reduce costs; second, overcome the problem of poor stability of adsorbent materials in complex wastewater environments, so that they can maintain good adsorption performance under different conditions and are not easily damaged; third, solve the problem of difficult regeneration, low regeneration efficiency or serious decline in adsorption performance after regeneration of existing materials, create adsorbent materials that are easy to regenerate and have little loss of adsorption performance after regeneration, and reduce the cost of use; fourth, improve the current situation of complex preparation process and expensive raw materials of existing high-performance adsorbent materials, explore simple and low-cost preparation methods, so that adsorbent materials are both economical and practical, and are convenient for large-scale promotion and application. Summary of the invention
[0007] The purpose of the present invention is to address the above shortcomings and provide a type of nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure, and a preparation method and application thereof. By introducing a rigid fluorene structural unit on the polymer main chain to increase the specific surface area of the polymer, the adsorption sites on the adsorbent surface are increased, thereby improving its adsorption performance, and at the same time, the thermal stability of the polymer material can also be improved. Rigid fluorene has a unique large-volume twisted non-coplanar structure. By introducing it into a nitrogen-rich porous adsorbent system, it is expected to utilize the spatial characteristics and template effect of the fluorene structure to effectively increase the specific surface area of the adsorbent, provide many contact sites for acidic orange 7 molecules, and interact with acidic orange 7 to adsorb and remove them. The adsorbent material should be renewable and recyclable, and the adsorbed acidic orange 7 can be desorbed by simple methods such as acid-base elution and heating to restore the adsorption capacity.
[0008] To achieve the above object, the present invention is implemented by the following technical solutions:
[0009] The present invention provides a nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure, wherein the structural formula of the adsorbent material containing a rigid fluorene structure is:
[0010]
[0011] In the formula 1, x=0.00-0.30, 1-x=0.70-1.00; more preferably, x=0.15-0.30, 1-x=0.70-0.85.
[0012] The molar percentage content of the functionalized structural unit (x*100%)=0.00-30%, and the molar percentage content of the non-functionalized structural unit (1-x)*100%=70-100%.
[0013] In a first aspect, the present invention provides a method for preparing a melamine-based adsorption material, comprising the following steps:
[0014] Under nitrogen protection, melamine, 4,4'-(9-fluorenyl)diphenylamine and terephthalaldehyde are dissolved in a three-necked flask with an organic solvent, and then heated and stirred for reaction. After solid precipitation, it is filtered and dried to obtain the nitrogen-rich porous organic adsorbent material shown in Formula 1.
[0015] Preferably, the molar ratio of the amino group to the aldehyde group is 5:3 to 9:7; the reaction temperature of the above reaction is 150 to 180° C., and the reaction time is 48 to 72 hours.
[0016] Preferably, the organic solvent is dimethyl sulfoxide, and its usage is 10 to 20 times the mass of melamine, 4,4'-(9-fluorenyl)diphenylamine and terephthalaldehyde.
[0017] The molar ratio of 4,4'-(9-fluorenylidene)diphenylamine to melamine is 0:1 to 0.3:0.7. Preferably, the molar ratio of 4,4'-(9-fluorenylidene)diphenylamine to melamine is 0.1:1 to 0.3:0.7.
[0018] The present invention also provides an application of the nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure, which is to use the adsorbent material in the adsorption of acid orange 7 dye in water.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention designs and synthesizes a type of nitrogen-rich porous adsorbent material containing a rigid fluorene structure, and introduces a rigid fluorene structure on the polymer main chain. Diphenylfluorene is an organic compound with a rigid twisted non-coplanar structure, and its unique structural characteristics make it have potential application value in the field of materials science. When the rigid fluorene non-coplanar structure is introduced into the nitrogen-rich porous adsorbent system, the fluorene molecule can play a multi-faceted role in the formation process of the adsorbent. On the one hand, the rigid structure of fluorene can produce a steric hindrance effect, preventing the adsorbent precursor from over-accumulating during the polymerization or assembly process, which is conducive to the formation of a looser and porous structure, thereby increasing the specific surface area.
[0021] (2) On the other hand, the fluorene molecule can act as a template to guide the formation and growth of the adsorbent pores, making the pore distribution more regular and uniform, further optimizing the pore structure of the adsorbent, and improving its selective adsorption capacity for adsorbates of different sizes. It can be used to adsorb acid orange 7 dye and form more binding sites with acid orange 7. Therefore, the development of nitrogen-rich porous adsorbents containing fluorene rigid structures has important scientific significance and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The synthetic route of the nitrogen-rich porous polymer containing the fluorene rigid structure of the present invention;
[0023] Figure 2 The infrared spectra of the nitrogen-rich porous polymers containing fluorene rigid structures described in Examples 1, 2, 3, 4, 5, and 6 of the present invention;
[0024] Figure 3 XRD diagram of the nitrogen-rich porous polymer containing fluorene rigid structure described in Examples 1, 2, 3, 4, 5, and 6 of the present invention;
[0025] Figure 4 The SEM images of the nitrogen-rich porous polymers containing fluorene rigid structures described in Examples 1, 2, 3, 4, 5, and 6 of the present invention;
[0026] Figure 5The N2 adsorption-desorption isotherms and pore size distribution curves of the nitrogen-rich porous polymers containing fluorene rigid structures described in Examples 1, 2, 3, 4, 5, and 6 of the present invention;
[0027] Figure 6 is a TGA graph of the nitrogen-rich porous polymer containing a fluorene rigid structure as described in Examples 1, 2, 3, 4, 5, and 6 of the present invention;
[0028] Figure 7 The effect of the amount of adsorbent on the adsorption performance of the nitrogen-rich porous polymer containing a fluorene rigid structure described in Example 5 of the present invention.
[0029] Figure 8 The figure shows the effect of the initial dye concentration on the adsorption performance of the nitrogen-rich porous polymer containing a fluorene rigid structure as described in Example 5 of the present invention.
[0030] Fig. 9 The effect of pH on the adsorption performance of the nitrogen-rich porous polymer containing a fluorene rigid structure described in Example 5 of the present invention.
[0031] Fig.10 The effect of time on the adsorption performance of the nitrogen-rich porous polymer containing a fluorene rigid structure described in Example 5 of the present invention.
[0032] Fig.11 The effect of temperature on the adsorption performance of the nitrogen-rich porous polymer containing a fluorene rigid structure described in Example 5 of the present invention.
[0033] Fig.12 This is a graph of the cyclic regeneration performance of the nitrogen-rich porous polymer containing a fluorene rigid structure described in Example 5 of the present invention. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention will be described in more detail below in conjunction with the accompanying drawings and specific examples.
[0035] The sources of the drugs and reagents described in the examples are as follows:
[0036] Melamine: Shanghai MacLean Biochemical Technology Co., Ltd., ≥98.0%
[0037] 4,4'-(9-fluorenyl)diphenylamine: Shanghai MacLean Biochemical Technology Co., Ltd., ≥97.0%
[0038] Terephthalaldehyde: Shanghai McLean Biochemical Technology Co., Ltd., ≥99.0%
[0039] Acid Orange 7: Anaiji Chemical, ≥98%
[0040] Dimethyl sulfoxide: Shanghai Lingfeng Chemical Reagent Co., Ltd., ≥98%
[0041] Anhydrous methanol: Shanghai Lingfeng Chemical Reagent Co., Ltd., 99%
[0042] Dichloromethane: Shanghai Lingfeng Chemical Reagent Co., Ltd., AR
[0043] Tetrahydrofuran: Shanghai Lingfeng Chemical Reagent Co., Ltd., ≥99.5%
[0044] Embodiment 1:
[0045] A method for preparing a type of rigid fluorene-containing nitrogen-rich porous organic polymer material comprises the following steps:
[0046] (1) Preparation of nitrogen-rich porous organic polymers with 0% fluorene content
[0047] Under nitrogen atmosphere, 0.8048g (6mmol) of terephthalaldehyde, 0.08412g (6.67mmol) of melamine and 30mL of dimethyl sulfoxide were added to a 100mL three-necked flask, stirred at 120°C for 20min, and heated to 170°C after being fully dissolved, and the reaction was continued for 72h. After cooling to room temperature, 30mL of anhydrous methanol was added to extract impurities and residual reactants for 1 hour. Then, the white solid was separated and washed three times with countless methanol, tetrahydrofuran and dichloromethane respectively. Finally, the white solid was dried in a vacuum oven at 120°C for 12 hours.
[0048] The synthetic route of the above preparation method is as follows Figure 1 shown.
[0049] Embodiment 2:
[0050] A method for preparing a nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure comprises the following steps:
[0051] (1) Preparation of nitrogen-rich porous organic polymers with 10% fluorene content
[0052] Under nitrogen atmosphere, 0.8048g (6mmol) of terephthalaldehyde, 0.7828g (6.21mmol) of melamine, 0.2403g (0.69mmol) of 4,4'-(9-fluorinated) diphenylamine and 30mL of dimethyl sulfoxide were added to a 100mL three-necked flask, stirred at 120°C for 20min, and heated to 170°C after being fully dissolved, and the reaction was continued for 72h. After cooling to room temperature, 30mL of anhydrous methanol was added to extract impurities and residual reactants for 1 hour. Then, the yellow solid was separated and washed three times with countless methanol, tetrahydrofuran and dichloromethane respectively. Finally, the yellow solid was dried in a vacuum oven at 120°C for 12 hours.
[0053] Embodiment 3:
[0054] A method for preparing a nitrogen-rich porous adsorbent material containing a rigid fluorene structure comprises the following steps:
[0055] (1) Preparation of nitrogen-rich porous organic polymer with 15% fluorene content
[0056] Under nitrogen atmosphere, 0.8048g (6mmol) of terephthalaldehyde, 0.7523g (5.96mmol) of melamine, 0.3668g (1.05mmol) of 4,4'-(9-fluorinated) diphenylamine and 30mL of dimethyl sulfoxide were added to a 100mL three-necked flask, stirred at 120°C for 20min, and heated to 170°C after being fully dissolved, and the reaction was continued for 72h. After cooling to room temperature, 30mL of anhydrous methanol was added to extract impurities and residual reactants for 1 hour. Then, the yellow solid was separated and washed three times with countless methanol, tetrahydrofuran and dichloromethane respectively. Finally, the yellow solid was dried in a vacuum oven at 120°C for 12 hours.
[0057] Example 4
[0058] A method for preparing a nitrogen-rich porous adsorbent material containing a rigid fluorene structure comprises the following steps:
[0059] (1) Preparation of nitrogen-rich porous organic polymers with 20% fluorene content
[0060] Under nitrogen atmosphere, 0.8048g (6mmol) of terephthalaldehyde, 0.7027g (5.71mmol) of melamine, 0.4977g (1.43mmol) of 4,4'-(9-fluorinated) diphenylamine and 30mL of dimethyl sulfoxide were added to a 100mL three-necked flask, stirred at 120°C for 20min, and heated to 170°C after being fully dissolved, and the reaction was continued for 72h. After cooling to room temperature, 30mL of anhydrous methanol was added to extract impurities and residual reactants for 1 hour. Then, the yellow solid was separated and washed three times with countless methanol, tetrahydrofuran and dichloromethane respectively. Finally, the yellow solid was dried in a vacuum oven at 120°C for 12 hours.
[0061] Embodiment 5:
[0062] A method for preparing a nitrogen-rich porous adsorbent material containing a rigid fluorene structure comprises the following steps:
[0063] (1) Preparation of nitrogen-rich porous organic polymers with 25% fluorene content
[0064] Under nitrogen atmosphere, 0.8048g (6mmol) of terephthalaldehyde, 0.6879g (5.45mmol) of melamine, 0.6336g (1.82mmol) of 4,4'-(9-fluorenyl)diphenylamine and 30mL of dimethyl sulfoxide were added to a 100mL three-necked flask, stirred at 120°C for 20min, and heated to 170°C after being fully dissolved, and the reaction was continued for 72h. After cooling to room temperature, 30mL of anhydrous methanol was added to extract impurities and residual reactants for 1 hour. Then, the yellow solid was separated and washed three times with countless methanol, tetrahydrofuran and dichloromethane respectively. Finally, the yellow solid was dried in a vacuum oven at 120°C for 12 hours.
[0065] Embodiment 6:
[0066] A method for preparing a nitrogen-rich porous adsorbent material containing a rigid fluorene structure comprises the following steps:
[0067] (1) Preparation of nitrogen-rich porous organic polymers with 30% fluorene content
[0068] Under nitrogen atmosphere, 0.8048g (6mmol) of terephthalaldehyde, 0.7027g (5.18mmol) of melamine, 0.4977g (2.22mmol) of 4,4'-(9-fluorinated) diphenylamine and 30mL of dimethyl sulfoxide were added to a 100mL three-necked flask, stirred at 120°C for 20min, and heated to 170°C after being fully dissolved, and the reaction was continued for 72h. After cooling to room temperature, 30mL of anhydrous methanol was added to extract impurities and residual reactants for 1 hour. Then, the yellow solid was separated and washed three times with countless methanol, tetrahydrofuran and dichloromethane respectively. Finally, the yellow solid was dried in a vacuum oven at 120°C for 12 hours.
[0069] The basic properties of the nitrogen-rich porous adsorbent material containing a rigid fluorene structure obtained in the above examples are shown in Table 1.
[0070] Table 1
[0071]
[0072]
[0073] In the table: Test conditions: temperature 30°C, pH 7; initial concentration of acid orange 7 solution 100 mg / L; adsorbent dosage 0.01 g; S BET , pore volume and average pore diameter were characterized by nitrogen adsorption-desorption experiments at 77K.
[0074] As can be seen from Table 1, the NRFPPs adsorbent material prepared by the present invention is characterized by nitrogen adsorption and desorption experiments ( Figure 5 ) has a specific surface area value ranging from 98.98 m2 .g -1 Up to 502.63m 2 .g -1 The specific surface area of the adsorbent increases gradually from NRFPP-1 to NRFPP-6, which is attributed to the increase in the content of 4,4'-(9-fluorenyl)diphenylamine in the reaction system, which increases the free volume in the polymer.
[0075] At the same time, it can be seen from Table 1 that when the adsorbent does not contain fluorene groups, the adsorption amount of acid orange 7 is 88.96 mg / g, and when the proportion of fluorene diamine is 25%, the adsorption amount of acid orange 7 by the adsorbent is 146.91 mg / g. With the increase of the content of fluorene structural units, the adsorption effect of the adsorbent on acid orange 7 increases significantly. When the proportion of fluorene diamine increases to 30%, the adsorption amount of acid orange 7 by the adsorbent is 148.53 mg / g, and the adsorption effect is not significantly improved compared with NRFPP-5. Considering the economic benefits, the proportion of fluorene diamine in the adsorbent is controlled at about 25% to achieve an ideal adsorption effect.
[0076] like Figure 3 As shown in the figure, the XRD spectra of the prepared series of porous polymers show a broad and stable peak at 23°, indicating that NRFPPs are mainly amorphous structures. The introduction of branched structures and large free volume fluorene structures destroys the regularity of molecular weight and makes it difficult to form crystals. The surface morphology of NRFPPs was tested by SEM, as shown in the figure. Figure 4 (a~f correspond to NRFPP-1~6) As shown in the figure, it can be seen that the NRFPP-1~6 series samples all have a stable sponge-like porous structure, a rough surface and loose irregular particles, which provide a large number of active sites for adsorbing dye molecules. The thermal stability of NRFPP-1~6 was studied by TGA. Figure 6 This is its thermal weight loss curve in a nitrogen atmosphere. From the figure, we can see that the thermal stability of NRFPPs increases as the content of fluorene structural units increases.
[0077] The adsorbent will face various complex environments during actual use. Optimizing the adsorption conditions can maximize the adsorption effect of the adsorbent. Taking NRFPP-5 as an example, the adsorption amount of acid orange 7 by the adsorbent under various conditions (such as Figures 7 to 11 ). Figure 7 The effect of adsorbent dosage on adsorption is that increasing the amount of adsorbent can significantly improve the adsorption effect of the adsorbent on Acid Orange 7, but the adsorption per unit mass decreases slightly. At this time, the binding sites of Acid Orange 7 and the adsorbent have reached the maximum capacity. If the amount of adsorbent is further increased, the adsorption effect will not be significantly improved. Figure 8It can be seen that with the increase of the concentration of Acid Orange 7, the adsorption amount per unit mass also increases. The main reason for this phenomenon is that increasing the concentration of Acid Orange 7 solution can provide a driving force to overcome the resistance of mass transfer of dye between the solid phase and the aqueous phase. In addition, with the increase of the initial concentration of Acid Orange 7, the adsorption effect of the adsorbent on Acid Orange 7 decreases slightly, but the decrease is very small. This is because the concentration of Acid Orange 7 solution is too high and part of the adsorbent has reached adsorption saturation and cannot be further adsorbed. Fig. 9 It can be seen that the adsorbent has the highest adsorption efficiency and adsorption capacity under neutral conditions (pH = 7). The adsorption effect of the adsorbent within 1200 minutes is as follows Fig.10 As shown in the figure, the adsorption of acid orange 7 increased rapidly in the first 30 minutes. This is because there are many adsorption sites on its surface, so the adsorbent has a rapid adsorption effect. As the adsorption sites gradually reach saturation, the adsorption effect gradually weakens. After 120 minutes of adsorption, the system reaches equilibrium. Fig.11 The effect of temperature on adsorption is that as the temperature increases from 303K to 333K, the adsorption amount shows a downward trend, which indicates that the adsorption process is an exothermic process. The higher the temperature, the weaker the adsorption capacity of the material. Within the conventional temperature range of application, the adsorbents all exhibit excellent adsorption performance. In summary, the optimal conditions for the adsorbent to adsorb Acid Orange 7 in aqueous solution are an initial concentration of 200 mg / L of Acid Orange 7, an adsorbent dosage of 0.005 g, a pH of 7, an adsorption time of 120 min, and an adsorption temperature of 303 K. Under conventional conditions, the maximum adsorption amount of Acid Orange 7 by the adsorbent is 189.44 mg / g. Under the conventional temperature and pH conditions of practical application, the adsorbent exhibits excellent adsorption capacity, indicating that it has broad application prospects in removing dye pollution in water.
[0078] As a key indicator, the regeneration performance of the adsorbent plays a decisive role in its effectiveness in practical application scenarios. After adsorbing acid orange 7, the NRFPPs were eluted with a 0.5 mol L-1 NaOH aqueous solution. Fig.12The adsorption efficiency of NRFPP-5 for acid orange 7 after four cycles is shown. The equilibrium adsorption capacity after the first cycle reached 187.55 mg / g. Compared with the original NRFPP-5, the regenerated NRFPP-5 showed good reusability and stability, and the data had significant consistency. After four cycles, its equilibrium adsorption capacity was 180.23 mg / g, and the adsorption capacity only declined slightly. This excellent reusability provides it with broad development prospects in long-term and large-scale water treatment application scenarios. The regeneration performance of the adsorbent containing fluorene structure is better, because the fluorene structure has a higher degree of conjugation and rigidity, which may enable the adsorbent to better maintain its structural integrity during the regeneration process, reduce the structural collapse or loss of active sites caused by the adsorption-desorption cycle, thereby improving the regenerativeness and recycling of the adsorbent. At the same time, the regeneration method of the adsorbent has the advantages of low energy consumption and easy operation compared with the traditional activated carbon thermal regeneration method.
[0079] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Without departing from the scope and technical principles of the described embodiments, many modifications and changes are obvious to those of ordinary skill in the art, and these modifications and changes should also be regarded as the scope of protection of the present invention.
Claims
1. A nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure, characterized in that: The molecular structural formula of the adsorbent material is: In the formula 1, x=0.00 to 0.30, 1-x=0.70 to 1.
00.
2. The nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure according to claim 1, characterized in that: In formula 1, x=0.15~0.30, 1-x=0.70~0.
85.
3. The method for preparing a nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure according to claim 1, characterized in that: The method comprises the following steps: under nitrogen protection, melamine, 4,4'-(9-fluorenyl)diphenylamine and terephthalaldehyde are added into a reaction container with an organic solvent to dissolve, then heated and stirred for reaction, solids are precipitated and filtered, and dried to obtain the nitrogen-rich porous organic adsorbent material shown in formula 1.
4. The method for preparing a nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure according to claim 3, characterized in that: The molar ratio of the amino group to the aldehyde group in the reactant is 5:3 to 9:
7.
5. The method for preparing a nitrogen-rich porous polymer adsorbent material containing a rigid fluorene structure according to claim 3, characterized in that: The reaction temperature is 150-180°C, and the reaction time is 48-72h.
6. The method for preparing a nitrogen-rich porous adsorbent material containing a rigid fluorene structure according to claim 3, characterized in that: The organic solvent is dimethyl sulfoxide, and the amount used is 10 to 20 times the total mass of melamine, 4,4'-(9-fluorenyl)diphenylamine and terephthalaldehyde.
7. The method for preparing a nitrogen-rich porous adsorbent material containing a rigid fluorene structure according to claim 3, characterized in that: The molar ratio of the amount of 4,4'-(9-fluorenyl)diphenylamine to melamine is 0:1 to 0.3:0.
7.
8. The use of a nitrogen-rich porous adsorbent material containing a rigid fluorene structure as claimed in claim 1, characterized in that: The adsorbent material can be used as a key component in an adsorption device and applied in wastewater treatment.
9. The use of a nitrogen-rich porous adsorbent material containing a rigid fluorene structure as claimed in claim 8, characterized in that: The wastewater is wastewater containing acid orange 7 dye.